Demand shuffle - a novel method for multi-level proportional lot sizing and scheduling - Alf Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
This contribution acquaints the reader with a model for multi-level single-machine proportional lot sizing and scheduling problems (PLSPs) that appear in the scope of short-term production planning. It is one of the first papers that deals with dynamic capacitated multi-level lot sizing and scheduling which is of great practical importance. The PLSP model refines well-known mixed-integer programming formulations for dynamic capacitated lot sizing and scheduling as for instance the DLSP or the CSLP. A special emphasis is given on a new method called ,,demand shuffle"' to solve multi-level PLSP instances efficiently but suboptimal. Although the basic idea is very simple, it becomes clear that in the presence of precedence and capacity constraints many non-trivial details are to be concerned. Computational studies show that the presented approach decidedly improves recent results.
Keywords: 650; Production planning; lot sizing; scheduling; multi-level; PLSP; heuristics; Produktionssteuerung; Mathematische Optimierung; Theorie